High Accumulation of a Heavy Metal in Ravenelia esculenta: An Edible Rust - Gandhi, K.R.; Deshpande, N.R.; Chaubal, Rohini (Asian Journal of Chemistry, 2016)
Ravenelia esculenta, edible rust infecting Acacia eburnea is consumed with relish in Maharashtra. Metal analysis of the host and parasite showed high percentage of aluminium in the parasite namely Ravenelia esculenta. So more consumption of this rust may lead to metabolic disorders such as Alzheimer’s disease, Parkinsonism etc. in human beings.